The Role of Endoscopy in the Resection of Sporadic Vestibular Schwannomas: A Systematic Review of Surgical Outcomes. Issue 1 (January 2022) - Raza-Knight, Saba; Chiuta, Sacha; Golash, Aprajay; Gurusinghe, Nihal; Roberts, Gareth; Alalade, Andrew F.
Abstract : Background: Vestibular schwannomas (VS) are benign intracranial tumors originating from the vestibular division of the eighth cranial nerve. Treatment options include microsurgery, radiotherapy, and surveillance. Endoscopy is becoming more widely used as an adjunct in skull base surgery and may influence outcomes in surgically managed VS. Methods: A systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies involving endoscope-assisted and fully endoscopic procedures for sporadic VS resection were identified. Facial nerve function, hearing preservation, extent of resection, and complications were analyzed. Results: Thirty-one studies were included (27 endoscope-assisted, four fully endoscopic). Subgroup analyses were performed to assess outcomes according to tumor size and surgical approach. Overall, endoscopic facial nerve preservation rates were comparable to microsurgical treatment. A subgroup analysis suggested that functional facial nerve preservation rates may be higher when endoscopic assistance is used for smaller (Koos I–II) tumors using the retrosigmoid or translabyrinthine approach. The gross total resection rate for small tumors was higher in retrosigmoid ES-assisted microsurgery (96.2%) compared to rates in the literature for the standard, open retrosigmoid approach. Hearing outcomes were more variable and were under-reported. Conclusions: Current data suggest that ES-assisted resection of sporadic VS is not inferior to microsurgical resection with respect to facial nerve outcomes and extent of resection. However, some ES series report poor hearing outcomes, which are under-reported in the literature. Further prospective studies are required to ascertain if endoscopic assistance can improve outcomes for VS resection, particularly for smaller (Koos I–II) tumors.